Filiação, adoção e psicanálise : análise da escuta grupal de pais que adotaram a partir dos eixos formadores da subjetividade - Gomes, Rafael de Souza Pereira (2022)
The present research, linked to the research line: Clinical Processes and Sociocultural Contexts of the Graduate Program in Psychology at the Federal University of Mato Grosso, aimed to listen to a group of parents who adopted and, for that, sought in the psychoanalytic theory the elements that could support the direction of this work. The post-adoption process can be considered as the initial moment of building bonds between parents and children that will enable the beginning of the filiation process, in general from the psychic’S point of view, this process is marked by numerous tensions between the members who will form a new family. Parents need to deal with the imaginary breaks that happen in relation to the idealized child and, above all, the issues related to what they have planned for this moment, along with that they need to be prepared to welcome this child who often has, in their history, countless experiences of neglect regarding the care they received throughout their lives and also ruptures IN very important moments in their development. REGARDING children and adolescents, who were adopted at an age after the age of three, it is necessary that they find elements so that they can address their questions to these new parents and that they are able to trust adults again. In this way, this can be a moment of intense psychological suffering for parents and children. In general, when this suffering is understood as something related to the children, they are taken to psychotherapeutic care, either in public or private institutions, but it is observed that parents have a difficulty in seeking help for their own suffering and consequently begin to suffer more for not being able to talk about their anxieties. Based on these findings, the present research carried out the creation of a group space where parents could talk freely about their experiences in relation to adoption and affiliation, understanding that this could be a place where they could elaborate their questions concerning this process. The experience consisted of twelve meetings with six parents, three couples. The group meetings took place in two periods; 1- from November to December 2019 three meetings were held in person and 2- from June to September 2020 there were nine meetings that took place online through the Skype platform. At the same time, a method of investigation WAS put in place about these parents' experiences and the process of affiliation, this research also undertook a method of treatment, as Freud teaches us, from the beginning, on psychoanalytic theory, as it enabled parents WITH A space where they could also re-signify their experiences. For the analysis of the parents' speeches and understanding of the experiences, the research proposed to analyze the material presented by the group from the four axes, also understood as psychic operations, forming subjectivity: 1- Subject's assumption; 2- Establishment of Demand; 3- Presence/absence alternation and 4- Paternal Function. These axes are present in the theoretical and practical basis of clinical research on Risk Indicators for Child Development - IRDI, research based on the theories of psychoanalysts Sigmund Freud, D. W. Winnicott and Jacques Lacan. Although according to the theoretical foundation of the IRDI research, these psychic operations must take place in the beginning of life, we propose in this work that they must be present in the parent-child relationship throughout their development, appearing in different ways on each moment of life, and that these are the necessary operations so that the filiation can happen and that they are axes that should guide the direction of the group listening of parents who adopted to provide that the filiation process can take place with the least possible psychic suffering.